KEGIATAN PENGEMBANGAN KEAKSARAAN BERBASIS PENDIDIKAN KARAKTER DI TAMAN KANAK-KANAK - Barokah Widuroyekti; Dwi Sambada; Tri Dyah Prastiti (LPPM Universitas Terbuka, 2016)
The study was aimed to develop character-education-based literacy activities through the children active involvement ofliteracy practice in kindergarten. In particular, the aim is (1) the analysis of the needs and constraints to obtain baseline data; (2) designing and developing a guidebook for character-based literacy activities with the active involvement of children in the literacy practice in kindergarten. The study was carried out by using a development research approach. The research subjects consisted of 22 kindergarten teachers and childrens from three kindergarten institutions. The research location is three kindergartens in Jombang, namely: TK Pembina Gudo, TK Negeri Pembina Jombang, and TK Al Wardah Peterongan. Data were collected through observation, interviews, scrutiny of documents, materials selection, and material mapping. Data were analyzed with descriptive techniques. Test the validity of product development validation performed by two groups of product development validator, the validator group practitioners/teachers (V1) and validator expert (V2). The results showed that the literacy hear-speak on a kindergartner who stand out include the ability to: retell stories read, perform songs, and participate in the conversation. As the literacy skills to read and write show the emergence of capabilities: holding the book from the right side, turning the page on the right side; show interest in writing; and draw/scribble and can tell by the picture. The result of the development is the Activity Books for Literacy Development Character-Education-Based, as a handbook for teachers.An assessment of the validity of product developmentcarried out on four aspects, namely the aspects of substance, presentation, linguistic, and graphic design. Validity test results showed that the quality of the product development of products in general have met the quality of